2016
DOI: 10.1007/s10493-016-0087-5
|View full text |Cite
|
Sign up to set email alerts
|

Factitious food for mass production of predaceous phytoseiid mites (Acari: Phytoseiidae) commonly found in Brazil

Abstract: Phytoseiid mites are commonly used as biological control agents of mite and small insect pests. To facilitate the production of phytoseiids, alternative food sources have been evaluated. The aim of this study was to evaluate the suitability of different food sources for the rearing of the phytoseiids Amblyseius tamatavensis Blommers, Euseius concordis (Chant) and Neoseiulus anonymus (Chant and Baker). This study evaluated the levels of oviposition of these predators when fed with 15 Astigmatina (Sarcoptiformes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 21 publications
0
19
1
5
Order By: Relevance
“…The suitability of a food source for a predator depends on both the nutritional content of the food and the nutritional requirement of the predator. An exclusive pollen diet is known to support the survival, development and reproduction of some phytoseiid species . It has already been demonstrated that N. californicus could survive, develop and oviposit successfully on a diet of almond pollen and maize pollen .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The suitability of a food source for a predator depends on both the nutritional content of the food and the nutritional requirement of the predator. An exclusive pollen diet is known to support the survival, development and reproduction of some phytoseiid species . It has already been demonstrated that N. californicus could survive, develop and oviposit successfully on a diet of almond pollen and maize pollen .…”
Section: Discussionmentioning
confidence: 99%
“…Supplementary food resources can be nutritionally limiting for predators or they can support high rates of development and reproduction . Some supplementary foods may enable only predator survival while prey are unavailable .…”
Section: Introductionmentioning
confidence: 99%
“…Nenhuma presa foi encontrada em associação com o predador. Após a coleta estes ácaros foram mantidos em unidades de criação similares àquelas descritas por McMurtry e Scriven (1965), alimentados com pólen de Typha domingensis Persoon e diferentes estágios de Thyreophagus cracentiseta Barbosa, Oconnor e Moraes Massaro et al, 2016).…”
Section: Methodsunclassified
“…Amblyseius tamatavensis é um típico representante deste grupo, que se alimenta de várias presas e outras fontes de alimento, como ácaros Astigmatina, tetraniquídeos, pólen, nematoides e ovos de pequenos insetos como a mosca-branca Massaro et a., 2016). Uma característica importante desta espécie é que pode ser facilmente criada de forma massal em laboratório quando alimentada com Thyreophagus cracentiseta Barbosa, OConnor & Moraes, ácaro do grupo Astigmatina (Massaro et al, 2019).…”
Section: Importância Agrícola De Amblyseius Tamatavensisunclassified
“…Embora tenha se notado um aumento do número de predadores sobre as plantas depois de um período de três semanas, este aumento foi pouco expressivo. O teste complementar realizado, em que os predadores foram liberados em plantas de C. ensiformis sem a adição de pólen, sugeriu que a presença de pólen de dendê em nada contribuiu para o diminuto aumento observado Massaro et al (2016). avaliaram os parâmetros biológicos de E. concordis quando alimentado com pólen de dendê, constatando que Naquele trabalho os predadores tiveram acesso apenas aos grãos de pólen como alimento (a unidade experimental era uma pequena placa de Petri cuja base era coberta por uma mistura de gesso e carvão).…”
unclassified